2016
DOI: 10.1021/acs.iecr.6b00461
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Steam Reforming and Steam Reforming of Methane, Isooctane, and N-Tetradecane over an Alumina Supported Spinel-Derived Nickel Catalyst

Abstract: The present work is focused on analyzing the potential of an alumina-supported spinel-derived nickel catalyst for oxidative steam reforming and steam reforming of model hydrocarbons present in gasoline and diesel, namely, isooctane and n-tetradecane, respectively. For comparative purposes these reforming processes have also been investigated for methane, and the catalytic behavior of a commercial rhodium catalyst has been evaluated as well. When operating with a relatively high volume hourly space velocity (eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…In some research, the nickel species were divided into three types depending on the different reduction temperatures, the free NiO, the “surface NiAl 2 O 4 ”, and the crystalline spinel NiAl 2 O 4 . Other research , also reported the same phenomenon in nickel-based alumina and named the reducible Ni 2+ species with α, β, and γ. However, it should be noticed that there is also a reduction peak of nickel species in their results when the temperature is less than 300 °C, which they both neglected.…”
Section: Resultsmentioning
confidence: 54%
See 1 more Smart Citation
“…In some research, the nickel species were divided into three types depending on the different reduction temperatures, the free NiO, the “surface NiAl 2 O 4 ”, and the crystalline spinel NiAl 2 O 4 . Other research , also reported the same phenomenon in nickel-based alumina and named the reducible Ni 2+ species with α, β, and γ. However, it should be noticed that there is also a reduction peak of nickel species in their results when the temperature is less than 300 °C, which they both neglected.…”
Section: Resultsmentioning
confidence: 54%
“…In addition, the NiAl 2 O 4 catalyst was reported for syngas production via dry re-forming of methane and the physical–chemical properties of the catalyst were discussed. Some research , also prepared the catalysts derived from NiAl 2 O 4 using different methods and applied them into oxidative steam re-forming and steam re-forming of methane. It was demonstrated that a spinel NiAl 2 O 4 catalyst is a more efficient catalyst with various chemical nature compared with commercial catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…The OSRM reaction provide safe operating conditions without need to supply of huge amount of external heat to run the process. Jimenez-Gonzalez et al [145] also studied the activity of Ni/γ-Al 2 O 3 catalyst in the oxidative steam reforming of methane, isooctane and N-tetradecane reactions. For comparison, authors tested the commercial Rh/Al 2 O 3 catalyst in these processes.…”
Section: The Catalytic Materials Used In the Oxy-steam Reforming Of Methane/lng Processmentioning
confidence: 99%
“…It is well known that the temperature distribution in the catalytic reactor can be optimized by a combination of steam reforming (1) and partial oxidation (3) reactions [20][21][22]. The oxidative steam reforming (OSR) of hydrocarbons and oxygenates is being studied not only to minimize the cold/hot spot effect in the catalytic reactor, but in some cases the reaction shows enhanced effectivity over steam reforming or partial oxidation [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Velu et al [20,21] found that methanol OSR was more efficient in many aspects than methanol SR and methanol PO for hydrogen production. Moreover, the presence of oxygen in the reaction mixture helps to control coking by the efficient removal of carbonaceous species produced during the reaction [22].…”
Section: Introductionmentioning
confidence: 99%